Cloning and characterization of a gene encoding an outer membrane protein required for siderophore-mediated uptake of Fe3+ in Pseudomonas putida WCS358. - Marugg, J D (1989)
In iron-limited environments plant-growth-stimulating Pseudomonas putida WCS358 produces a yellow-green fluorescent siderophore called pseudobactin 358. Ferric pseudobactin 358 is efficiently taken up by cells of WCS358 but not by cells of another rhizophere-colonizing strain, Pseudomonas fluorescens WCS374. A gene bank containing partial Sau3A DNA fragments from WCS358 was constructed in a derivative of the broad-host-range cosmid pLAFR1. By mobilization of this gene bank to strain WCS374 a cosmid clone, pMR, which made WCS374 competent for the utilization of pseudobactin 358 was identified. By subcloning of the 29.4-kilobase (kb) insert of pMR the essential genetic information was localized on a BglII fragment of 5.3 kb. Tn5 mutagenesis limited the responsible gene to a region of approximately 2.5 kb within this fragment. Since the gene encodes an outer membrane protein with a predicted molecular mass of 90,000 daltons, it probably functions as the receptor for ferric pseudobactin 358. The gene is flanked by pseudobactin 358 biosynthesis genes on both sides and is on a separate transcriptional unit. WCS374 cells carrying pMR derivatives with Tn5 insertions in the putative receptor gene did not produce the 90,000-dalton protein anymore and were unable to take up Fe3+ via pseudobactin 358. In WCS358 cells as well as in WCS374 cells the gene is expressed only under iron-limited conditions.